LAPAROSCOPIC DISTAL PANCREATECTOMY WITH SPLEEN PRESERVATION - PAIS-COSTA, Sergio Renato (Arq Bras Cir Dig, 2018)
BACKGROUND: Laparoscopic distal pancreatectomy has been the choice for resection of distal pancreas lesions due many advantages over open approach. Spleen preservation technique seems minimizes infectious complications in long-term outcome. AIM: To present the results of laparoscopic distal pancreatectomies with spleen preservation by Kimura´s technique (preservation of spleen blood vessels) performed by single surgical team. METHODS: Retrospective case series aiming to evaluate both short and long-term outcomes of laparoscopic distal pancreatectomies with spleen preservation. RESULTS: A total of 54 laparoscopic distal pancreatectomies were performed, in which 26 were laparoscopic distal pancreatectomies with spleen preservation by Kimura´s technique. Mean age was 47.9 years-old (21-75) where 61.5% were female. Mean BMI was 28.5 kg/m² (18-38.8). Mean diameter of lesion was 4.3 cm (1.8-7.5). Mean operative time was 144.1 min (90-200). Intraoperative bleeding was 119.2 ml (50-600). Conversion to laparotomy 3% (n=1). Postoperative morbidity was 11.5%. Postoperative mortality was null. Mean of hospital stay was 4.8 days (2-14). Mean time of follow-up period was 19.7 months (2-60). There was no neoplasm recurrence or mortality on evaluated period. There was no infectious complication. CONCLUSION: Laparoscopic distal pancreatectomy with spleen and splenic vessels preservation is feasible, safe, and effective procedure. This technique presented both low morbidity and null mortality on this sample. There were neither infectious complications nor neoplasm recurrence on long-term follow-up period.